Neuromyelitis optica spectrum disorders in patients with myasthenia gravis: ten new aquaporin-4 antibody positive cases and a review of the literature - Jarius, Sven; Wildemann, Brigitte (Multiple sclerosis journal, 2012)
Background:Neuromyelitis optica (NMO, Devic syndrome) and myasthenia gravis (MG) are rare antibody-mediated autoimmune disorders. Concurrent incidence has been reported in only few patients, mostly non-Caucasians.Objective:To report on ten Caucasian patients with NMO spectrum disorders (NMOSD) and MG and to provide a comprehensive review of the literature.Method:Retrospective study.Results:In total, 26 patients (m:f = 1:12; Caucasian in 12) with MG (generalized in 17) and NMOSD (NMO in 21, longitudinally extensive transverse myelitis in five) were identified from the authors? own files (n = 10) and the previous literature (n = 16). MG preceded NMOSD in 24/25 cases (96%). AQP4-Ab were tested in 20 patients and were positive in 17 (85%). Twenty out of 25 patients (80%) had been treated with thymectomy or thymic irradiation, which preceded NMOSD in all cases (median latency, 12 years; range, 0.3?32). At last follow-up, complete remission of MG was reported in 15/22 (68%), and MG was well controlled with pyridostigmine in three. Co-existing autoimmune disorders or autoimmune antibodies were reported in 17 patients.Conclusion:Our study demonstrates that i) AQP4-Ab-positive NMOSD are more commonly associated with MG in Caucasians than previously thought; ii) MG precedes NMOSD in most cases, often by more than a decade; iii) NMOSD almost exclusively occur in females with juvenile or early-onset MG; and iv) MG frequently takes an unusually mild course in patients with NMOSD. A history of thymectomy could be a possible risk factor for the later development of NMOSD. We recommend testing for AQP4-Ab in MG patients presenting with atypical motor or optic symptoms.